IMPLEMENTATION OF PRINCIPAL SUPERVISION IN PRIMARY SCHOOL - Kusumawarti, Etika; Ahmad, Hariyatunnisa (Social, Humanities, and Educational Studies (SHEs): Conference Series, 2018)
Management is the process of determining the goals or objectives to be achieved and determining the paths and sources used to achieve the objectives. The purpose of this study was to describe the principal's supervision activities and find out the effectiveness of education management in elementary schools. The research data was obtained from the school principal and class teacher in elementary school. The results showed (1) elementary academic supervision activities carried out through three steps, namely planning, implementing, and following up activities and (2) supervision activities had a positive impact on learning management carried out by elementary school teachers. Management of education in primary schools is carried out by planning, implementing, and following up. Educational goals that have been determined by the school can be achieved through the learning process, so that the management of education in elementary schools can be said to be effective